Penerapan Tax Amnesty, Pelayanan Perpajakan, Sanksi Perpajakan, dan Penerimaan Pajak - Dewi, Ni Putu Anggun Kencana; Jati, I Ketut (E-Jurnal Akuntansi, 2024)
Taxes are contributions to the state with the function of funding development and government spending. The research was conducted with the aim of explaining the effect of implementing Tax Amnesty, Tax Services, and Tax Sanctions at the East Denpasar Pratama Tax Service Office. The technique used in data collection is Purposive Sampling by means of research samples using all Individual and Corporate Taxpayers provided they have participated in the Tax Amnesty program at KPP Pratama East Denpasar. The Multiple Linear Regression Analysis Method was used in hypothesis testing with the results that Tax Amnesty, Tax Services, Tax Sanctions had a positive effect on tax revenues at the East Denpasar Primary Tax Service Office. Keywords: Tax Amnesty; Tax Services; Tax Sanctions; Tax Revenue